2022
DOI: 10.1371/journal.pone.0262891
|View full text |Cite
|
Sign up to set email alerts
|

Sources of genomic diversity in the self-fertile plant pathogen, Sclerotinia sclerotiorum, and consequences for resistance breeding

Abstract: The ascomycete, Sclerotinia sclerotiorum, has a broad host range and causes yield loss in dicotyledonous crops world wide. Genomic diversity was determined in a population of 127 isolates obtained from individual canola (Brassica napus) fields in western Canada. Genotyping with 39 simple sequence repeat (SSR) markers revealed each isolate was a unique haplotype. Analysis of molecular variance showed 97% was due to isolate and 3% due to geographical location. Testing of mycelium compatibility among 133 isolates… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
2
1
0
Order By: Relevance
“…Variation in S. sclerotiorum isolate aggressiveness has been reported previously on numerous crop hosts, including sunflower ( Ekins et al, 2007 ; Otto-Hanson et al, 2011 ; Taylor et al, 2015 ; Denton-Giles et al, 2018 ; Yu et al, 2020 ; Rather et al, 2022 ). We observed only a modest correlation between isolate aggressiveness on the two sunflower inbred lines, consistent with observations of genotype-isolate interactions for S. sclerotiorum isolates evaluated on crop hosts such as soybean, canola, and sunflower ( Davar et al, 2011 ; Ge et al, 2012 ; Willbur et al, 2017 ; Buchwaldt et al, 2022 ). Resistance to S. sclerotiorum is quantitative rather than governed by single, dominant resistance genes characteristic of gene-for-gene interactions commonly observed in plant interactions with biotrophic pathogens.…”
Section: Discussionsupporting
confidence: 89%
“…Variation in S. sclerotiorum isolate aggressiveness has been reported previously on numerous crop hosts, including sunflower ( Ekins et al, 2007 ; Otto-Hanson et al, 2011 ; Taylor et al, 2015 ; Denton-Giles et al, 2018 ; Yu et al, 2020 ; Rather et al, 2022 ). We observed only a modest correlation between isolate aggressiveness on the two sunflower inbred lines, consistent with observations of genotype-isolate interactions for S. sclerotiorum isolates evaluated on crop hosts such as soybean, canola, and sunflower ( Davar et al, 2011 ; Ge et al, 2012 ; Willbur et al, 2017 ; Buchwaldt et al, 2022 ). Resistance to S. sclerotiorum is quantitative rather than governed by single, dominant resistance genes characteristic of gene-for-gene interactions commonly observed in plant interactions with biotrophic pathogens.…”
Section: Discussionsupporting
confidence: 89%
“…This was further confirmed by the complete MLST sequence and UP-PCR profile identity of French and New Zealand isolates, as reported in Figure 4 [47][48][49]. Studies on the diversity within the Sclerotiniacae family showed that variability among strains can be very high [50], but it can also be very limited in space and time [51], suggesting the need to better decipher the different genetic backgrounds of Sclerotiniaceae undergoing fast genetic changes, or on the contrary, high genetic stability.…”
Section: Discussionsupporting
confidence: 55%
“…Clonality was most prevalent among the Australian strains, whereas European and North American strains were mostly genotypically distinct (Figure 1). This was expected because most of the European and North American strains were previously shown to be distinct lineages using markers [48,49], whereas 99 of the Australian strains were collected from five sites (two of which were in the same locality) in Western Australia with no prior genotyping [50,51].…”
Section: Resultsmentioning
confidence: 99%